In vitro versus in situ biofilms for evaluating the antimicrobial effectiveness of herbal mouthrinses - Schönbächler, Nicole; Thurnheer, Thomas; Paqué, Pune Nina; Attin, Thomas; Karygianni, Lamprini (Frontiers in Cellular and Infection Microbiology, 2023)
For centuries, diverse mouthrinses have been applied for medicinal purposes in the oral cavity. In view of the growing resistance of oral microorganisms against conventional antimicrobial agents e.g. chlorhexidine, the implementation of alternative treatments inspired by nature has lately gained increasing interest. The aim of the present study was to compare in vitro biofilm models with in situ biofilms in order to evaluate the antimicrobial potential of different natural mouthrinses. For the in vitro study a six-species supragingival biofilm model containing A. oris, V. dispar, C. albicans, F. nucleatum, S. mutans and S. oralis was used. Biofilms were grown anaerobically on hydroxyapatite discs and treated with natural mouthrinses Ratanhia, Trybol and Tebodont. 0.9% NaCl and 10% ethanol served as negative controls, while 0.2% CHX served as positive control. After 64h hours, biofilms were harvested and quantified by cultural analysis CFU. For the in situ study, individual test splints were manufactured for the participants. After 2h and 72h the biofilm-covered samples were removed and treated with the mouthrinses and controls mentioned above. The biofilms were quantified by CFU and stained for vitality under the confocal laser scanning microscope. In the in vitro study, 0.2% CHX yielded the highest antimicrobial effect. Among all mouthrinses, Tebodont (4.708 ± 1.294 log10 CFU, median 5.279, p<0.0001) compared with 0.9% NaCl showed the highest antimicrobial potential. After 72h there was no significant reduction in CFU after 0.2% CHX treatment. Only Trybol showed a statistically significant reduction of aerobic growth of microorganisms in situ (5.331 ± 0.7350 log10 CFU, median 5.579, p<0.0209). After treatment with the positive control 0.2% CHX, a significant percentage of non-vital bacteria (42.006 ± 12.173 log10 CFU, median 42.150) was detected. To sum up, a less pronounced effect of all mouthrinses was shown for the in situ biofilms compared to the in vitro biofilms.